ASEAN+3 bond market guide 2017 Lao People Democratic Republic. (Metro Manila, Philippines Asian Development Bank, 2017)
The purpose of this Bond Market Guide is to provide an update to current and future domestic, regional, and international market participants on the tremendous developments in the Lao People Democratic Republic (Lao PDR) securities market since the first publication of the Bond Market Guide in 2012.
Keywords: Bonds -- Lao People Democratic Republic; Fiscal policy -- Economic aspects; Electronic books